2016
DOI: 10.1080/03650340.2016.1235268
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of chabazite- and mordenite-rich tuffs, and their mixtures as soil amendments and slow release fertilizers

Abstract: In the present study, zeolite tuffs of diverse chemistry, mineralogy and origin were characterized and tested for their efficiency as slow release fertilizers (SRF) through a series of leaching tests. Mixtures of zeolite tuffs were created and tested as loamy soil additives, in order to evaluate any synergistic effect on their cation exchange capacity (CEC) and SRF properties. The studied materials were a chabazite-rich tuff (SOR), a mordenite-rich tuff (KIM), 3 mixtures of them (SOR/KIM 30/70, 50/50 and 70/30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…According to their chemistry, all tuffs studied exhibit shoshonitic affinity and trachytic composition (Figure 2). All Italian tuffs studied have different mineralogy and chemistry compared to those originated from the Balkans and Hungary which are rich in clinoptilolite and/or mordenite and are also used in construction (building stones and cement raw material) [5,23,24]. 2.…”
Section: Resultsmentioning
confidence: 99%
“…According to their chemistry, all tuffs studied exhibit shoshonitic affinity and trachytic composition (Figure 2). All Italian tuffs studied have different mineralogy and chemistry compared to those originated from the Balkans and Hungary which are rich in clinoptilolite and/or mordenite and are also used in construction (building stones and cement raw material) [5,23,24]. 2.…”
Section: Resultsmentioning
confidence: 99%
“…The zeolite-rich SOR sample had the highest pH value (Table 5), which is common in this type of rocks (Stamatakis et al, 2017), whereas the opal-A rich ELS sample showed the lowest pH value. SOR was the only sample to have an effect on OOMW pH (5.01), neutralising it to 6.96 after 24 h of treatment.…”
Section: Phmentioning
confidence: 93%
“…The poorest value was displayed by the opal-A-rich ELS sample, being in accordance with the Derkowski et al 2015measurements, where opal-A CEC was 8 cmol(+)/kg. The SOR chabazite tuff exhibited high CEC values, characteristic for such zeolite deposits (Stamatakis et al, 2017). CYP and SAM samples had intermediate values, due to the coexistence of minerals with diverse CEC (zeolites, clay minerals and opal-CT).…”
Section: Cecmentioning
confidence: 98%
See 1 more Smart Citation
“…This volcanic activity during Pleiocene is related to the significant industrial mineral deposits of the island. The genesis, properties and applications of the zeolite and bentonite deposits have been extensively studied (Fragoulis et al, 1997;Christidis, 1998b;Stamatakis et al, 1998Stamatakis et al, , 2000Stamatakis et al, , 2017Giannatou et al, 2016).…”
Section: Bentonite Clay From Kimolos Island (Sw Cyclades Greece)mentioning
confidence: 99%